2008
DOI: 10.1007/s12105-007-0040-3
|View full text |Cite
|
Sign up to set email alerts
|

Hamartomatous Angiolipoma of the Parotid Gland (Sialoangiolipoma)

Abstract: Mesenchymal tumors of the salivary glands are rare and mostly localized to the parotid gland. We report on the clinico-pathological features of a distinct parotid tumor occurred in a newborn, showing glandular structures admixed with mature lipocytes and blood vessels in variable proportions. This was a well-circumscribed and slowly growing nodule of the superficial parotid lobe, mostly reddish in color with white-yellowish striations. Microscopically, a distinct lobular architecture was evident, along with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Spindle cell lipoma [37], osteolipoma [38], fibrolipoma [39], angiolipoma [40], lipoblastoma [41], hibernoma [42], and pleomorphic lipoma [43] are the main subtypes reported. Of these, spindle cell lipoma may mimic myoepithelioma with extensive lipometaplasia.…”
Section: Rare Lipoma Variantsmentioning
confidence: 99%
“…Spindle cell lipoma [37], osteolipoma [38], fibrolipoma [39], angiolipoma [40], lipoblastoma [41], hibernoma [42], and pleomorphic lipoma [43] are the main subtypes reported. Of these, spindle cell lipoma may mimic myoepithelioma with extensive lipometaplasia.…”
Section: Rare Lipoma Variantsmentioning
confidence: 99%
“…[1] These comprise the angiomas, schwannomas, neurofibromas, lipomas and rarely hibernomas, lipoblastoma and pleomorphic/spindle cell lipomas. [1] Combined mesenchymal tumors like sialolipoma, lipoadenomas, angiolipomas have been described only exceptionally in salivary glands with most of the cases being reported in parotid gland. [14] Only four cases of sialolipomas have been described till now in the submandibular gland with three occurring in adults and one in a child.…”
mentioning
confidence: 99%
“…[1] Combined mesenchymal tumors like sialolipoma, lipoadenomas, angiolipomas have been described only exceptionally in salivary glands with most of the cases being reported in parotid gland. [14] Only four cases of sialolipomas have been described till now in the submandibular gland with three occurring in adults and one in a child. [4] However, to the best of our knowledge, no case of submandibular gland hamartoma comprising such myriad structures including salivary gland ducts, skeletal muscle fibers and nerve within a vessel wall has been described in literature.…”
mentioning
confidence: 99%
“…Maiorano et al 11 reported on the clinicopathological features of a distinct parotid tumour in a newborn, showing normal glandular structures admixed with mature lipocytes and blood vessels in variable proportions, and identified the pathology as a sialoangiolipoma. However, as it was composed of normal-looking acinar and ductal structures, interposed with mature lipocytes and blood vessels, it has indigenous tissues admixed with mature tissues and thus it fits into the Willis definition of a hamartoma 2.…”
Section: Discussionmentioning
confidence: 99%